A comparison of functional outcomes in patients undergoing revision arthroscopic repair of massive rotator cuff tears with and without arthroscopic suprascapular nerve release - Savoie III FH; Zunkiewicz M; Field LD; Replogle WH; O'Brien MJ (Dove Medical Press, 2016)
Felix H Savoie III,1 Mark Zunkiewicz,2 Larry D Field,2 William H Replogle,3 Michael J O’Brien1 1Tulane Institute of Sports Medicine, Tulane University School of Medicine, New Orleans, LA, USA; 2Mississippi Sports Medicine and Orthopaedic Center, Jackson, MS, USA; 3Department of Family Medicine, University of Mississippi Medical Center, Jackson, MS, USA Purpose: This study was designed to compare functional outcomes in patients undergoing revision repair of massive rotator cuff tears (retracted medial to the glenoid) with Goutallier Grade 4 atrophy and concomitant release of the suprascapular nerve to a similar group of patients with Grade 3 atrophy undergoing revision rotator cuff repair (RTCR) without nerve release. We hypothesized that patients undergoing nerve release would have more favorable functional outcomes as measured by the Modified University of California at Los Angeles shoulder rating scale (UCLA). Patients and methods: Twenty-two patients underwent revision repair of massive rotator cuff tears with release of the suprascapular nerve at the suprascapular notch. We compared total preoperative, postoperative, and change in UCLA score in these patients to a similar group of 22 patients undergoing revision RTCR without suprascapular nerve release. Additionally, UCLA subscores between the two groups were compared preoperatively and at final follow-up. Results: The average preoperative UCLA score in the nerve-release group was 7.91, and final follow-up average was 27.86; average 3.05 grades of strength were recovered. In the comparison group, average preoperative UCLA score was 11.77, and final follow-up average was 29.09; average 1.32 grades of strength were recovered. The average preoperative UCLA score was significantly worse in the nerve-release group (P=0.007). The average postoperative UCLA score was not significantly different (P=0.590) between the groups, indicating a better improvement in the nerve-release group with significantly greater improvement in active forward flexion, strength, and pain relief. Conclusion: Patients who underwent concomitant release of the suprascapular nerve during revision RTCR had greater overall improvement as noted in pain relief, active forward flexion, and strength, than a comparable group without nerve release. Keywords: muscle atrophy, suprascapular nerve release, revision rotator cuff repair, atrophy